2011
DOI: 10.3945/jn.110.132613
|View full text |Cite
|
Sign up to set email alerts
|

Food Prices Are Associated with Dietary Quality, Fast Food Consumption, and Body Mass Index among U.S. Children and Adolescents

Abstract: Food prices are expected to affect dietary intakes, however, previous findings are mixed and few are based on nationally representative data. We examined the associations of price indices of fast foods (FF-PI) and fruits and vegetables (FV-PI) with dietary intakes and BMI among U.S. children and adolescents using data from the Continuing Survey of Food Intakes by Individuals (CSFII; 1994-1998) for 6759 children (2-9 y) and 1679 adolescents (10-18 y). FF-PI and FV-PI were linked to individuals' CSFII dietary da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 24 publications
0
47
0
1
Order By: Relevance
“…According to Beydoun et al [47], 'food [relative] prices are associated with dietary quality, fast-food consumption and body mass index among US children and adolescents.' f More specifically, this study shows that lower prices of fruit and vegetables are associated with greater fiber consumption and reduced body mass index and higher fast-food prices are associated with lower consumption of fast foods and higher consumption of dietary fibers, dairy products, calcium and fruit and vegetables.…”
Section: Economic Factorsmentioning
confidence: 99%
“…According to Beydoun et al [47], 'food [relative] prices are associated with dietary quality, fast-food consumption and body mass index among US children and adolescents.' f More specifically, this study shows that lower prices of fruit and vegetables are associated with greater fiber consumption and reduced body mass index and higher fast-food prices are associated with lower consumption of fast foods and higher consumption of dietary fibers, dairy products, calcium and fruit and vegetables.…”
Section: Economic Factorsmentioning
confidence: 99%
“…Food affordability, and specifically food and restaurant prices, has been found to exert generally small effects on body weight outcomes, although these findings also seem to vary by socioeconomic status, with the association between prices and body weight stronger among socioeconomically disadvantaged populations (Beydoun, Powell, Chen, & Wang, 2011;Powell & Chaloupka, 2009). Among children, relatively higher food prices of fruits and vegetables have been associated with lower frequency of fruit and vegetable intake (Sturm & Datar, 2011), lower fiber intake, and higher weight (Beydoun et al, 2011). In addition, relative higher prices of fast food have been associated with better diet quality among young children (Beydoun et al, 2011).…”
Section: Food Affordabilitymentioning
confidence: 89%
“…Among children, relatively higher food prices of fruits and vegetables have been associated with lower frequency of fruit and vegetable intake (Sturm & Datar, 2011), lower fiber intake, and higher weight (Beydoun et al, 2011). In addition, relative higher prices of fast food have been associated with better diet quality among young children (Beydoun et al, 2011).…”
Section: Food Affordabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that access to low-priced fresh fruit and vegetables is associated with lower BMI among 2-to 9-year-old children. 16 Supermarkets tend to have the most diverse, low-priced produce, compared to the four other categories of food establishments we examined. Because parents and families face both budget and time constraints, by living closer to supermarkets, it is likely more convenient for parents and children to purchase and consume produce on a more frequent basis and, as a result, foster a lower BMI z-score.…”
mentioning
confidence: 93%